Factors affecting the change scores of professors in higher education - Reza Mirarab; Abbas Hoseinijo (آموزش مهندسی ایران, 2016)
Evaluating educational progress of students as final step in learning systems, especially in engineering disciplines, is very important to have effective graduates. This study aimed to identify and interpret factors affecting and altering final scores of professors at the end of semester. To achieve this, a qualitative study based on an interpretation plan was conducted including interview with 22 professors in engineering disciplines at the two universities namely University of Mazandaran and Golestan University. Through content analysis and open coding, interviews were analyzed and categorization of data was perfored. Findings showed 6 factors namely expediency, superficiality, lifesaving, embarrassment, political orientation and incuriosity can be considered as factors affecting final scores of interviewed teachers. It is understood that under the effect of these factors, professor’s toleration lead to a meaningless and unfair educational evaluation system. These findings were validated by a survey conducted using a questionnaire. The sample included 131 professors in engineering disciplines at the two aforementioned universities. Gathered data were analyzed using descriptive statistics, one sample T-test and W test. Findings showed all of 6 factors, to some extent, have significant effect on final scores of professors at the end of semester. Expediency (0.45), superficiality (0.28) and lifesaving (0.24) are the three most important factors among all.